Efficacy and Safety of Vorapaxar as Approved for Clinical Use in the United States - Magnani, Giulia; Bonaca, Marc P.; Braunwald, Eugene; Dalby, Anthony J.; Fox, Keith A. A.; Murphy, Sabina A.; Nicolau, José Carlos; Oude Ophuis, Ton; Scirica, Benjamin M.; Spinar, Jindrich; Theroux, Pierre; Morrow, David A. (Journal of the American Heart Association, 2015)
Vorapaxar is a protease-activated receptor-1 antagonist approved by the U.S. Food and Drug Administration (FDA) for the reduction of thrombotic cardiovascular (CV) events in patients with a history of myocardial infarction (MI) and peripheral artery disease (PAD), without a previous stroke or transient ischemic attack (TIA). We examined the efficacy and safety of vorapaxar in the intended use population, considering 20,170 patients randomized in the multinational, double-blinded, placebo-controlled TRA 2°P-TIMI 50 trial. Of these, 16,897 qualified with a history of MI in the prior 2 weeks to 1 year and 3273 with PAD. At baseline 97% of the patients were treated with aspirin, 71% with a thienopyridine, and 93% a statin. At 3 years, the endpoint of CV death, MI, or stroke was significantly reduced with vorapaxar compared with placebo (7.9% versus 9.5%, HR, 0.80; 95% CI 0.73 to 0.89; P<0.001). Vorapaxar also significantly reduced the composite of CV death, MI, stroke, and urgent coronary revascularization (10.1% versus 11.8%, HR, 0.83; 95% CI 0.76 to 0.90; P<0.001), as well as the rate of CV death or MI (P<0.001). The safety endpoint of GUSTO moderate or severe bleeding, was increased in the vorapaxar group (3.7 versus 2.4, HR, 1.55; 95% CI 1.30 to 1.86, P<0.001). Intracranial bleeding (ICH) was 0.6% versus 0.4%, P=0.10 with vorapaxar versus placebo, with fatal bleeding 0.2% versus 0.2%; P=0.70. In patients with prior MI or PAD who have not had a previous stroke or TIA, vorapaxar added to standard therapy is effective for long-term secondary prevention of thrombotic CV events, while increasing moderate or severe bleeding. URL: clinicaltrials.gov Unique Identifier: NCT00526474.